Human embryology - Singh, Inderbir; Pal, G.P (Macmillan India Ltd., 2001)
This book discusses the development of various tissues and organs of the human body in a clear and concise manner. It also deals with phenomena that are closely related to the development of the embryo. Profuse, simple illustrations are key features which further facilitates a quick grasp of the concepts.